Clinical Characteristics and Treatment Outcomes of 65 Patients With BRAF-Mutated Non-small Cell Lung Cancer - Mu, Yuxin; Yang, Ke; Hao, Xuezhi; Wang, Yan; Wang, Lin; Liu, Yutao; Lin, Lin; Li, Junling; Xing, Puyuan (Frontiers in Oncology, 2020)
BRAF mutation is an oncogenic driver gene in non-small cell lung cancer (NSCLC) with low frequency. The data of patients with NSCLC harboring BRAF mutations is rare. We conducted a retrospective multicenter study in Chinese patients with NSCLC harboring BRAF mutations between Jan 2017 and Jul 2019. A total of 65 patients treated in 22 centers were included, 54 harbored BRAF-V600E mutation and 11 had non-V600E mutations, including K601E, G469S, G469V, G469A, G596R, G466R and T599dup. Of 18 patients with early-stage disease at diagnosis and underwent a resection, the median disease-free survival (DFS) was 43.2 months, 18.7 months and 10.1 months of stage I, II and IIIA patients, respectively. In 46 patients with advanced-stage disease at data cutoff, disease control rate (DCR) and progression-free survival (PFS) of first-line anti-BRAF targeted therapy was superior than chemotherapy in patients harboring BRAF-V600E mutation (DCR, 100.0% vs. 70.0%, P=0.027; median PFS, 9.8 months vs. 5.4 months, P=0.149). Of 30 V600E-mutated patients who received anti-BRAF therapy during the course of disease, median PFS of vemurafenib, dabrafenib, and dabrafenib plus trametinib was 7.8 months, 5.8 months and 6.0 months, respectively (P=0.970). Median PFS were similar between V600E and non-V600E patients (5.4 months vs. 5.4 months, P=0.825) to first-line chemotherapy. Nine patients were treated with checkpoint inhibitors, with median PFS of 3.0 months. Our data demonstrated the clinical benefit of anti-BRAF targeted therapy in Chinese NSCLC patients harboring BRAF-V600E mutation. The value of immunotherapy and treatment selection among non-V600E population needs further study.